Digital Marketing Entrepreneur Education for MSMEs - Dwi Putranto Riau; Abdurrahman Rahim Thaha (CV. DYOQU PUBLISHING MANAGEMENT, 2026)
Background: Digital marketing entrepreneur education for Micro, Small, and Medium Enterprises (MSMEs) is essential to developing digital businesses. With technological advances and the internet, digital marketing offers various opportunities for MSMEs to expand their markets and increase sales. In this digital era, many MSMEs still need to utilize online sales or are constrained by limited resources ranging from human resources, budget, infrastructure, and understanding of MSMEs in digital marketing. Aims: This study describes and analyzes the importance of digital marketing entrepreneur education for MSMEs. Methods: The method used in this study is descriptive qualitative. Primary data was collected on MSME batik artisans, and secondary data was collected through websites, mass media, journals, books, and others. Data analysis uses interactive analysis by performing data reduction steps, data presentation, and drawing conclusions or verification Result: The research is expected to produce concrete steps that can be taken in education to improve MSME businesses, namely Introduction to Digital Technology, Utilization of Social Media, Search Engine Optimization (SEO) and Search Engine Marketing (SEM), E-commerce and Online Sales Platforms, Performance Analysis and Measurement, Customer Relationship Management (CRM), Continuous Learning and Adaptation and Mentoring and Mentoring. Conclusion: Education is a crucial tool to enhance digital entrepreneur skills and guide MSME business growth.